Tau-Protein-Spiegel in der Diagnostik der Alzheimer-Demenz - Schönknecht, Peter; Pantel, Johannes; Werle, Egon; Hartmann, Tobias; Essig, Marco; Baudendistel, Klaus; Beyreuther, Konrad; Schröder, Johannes (Fortschritte der Neurologie, Psychiatrie, 2000)
Thieme E-Books & E-Journals